PERLINDUNGAN JAMSOSTEK TERHADAP PEKERJA WAKTU TERTENTU PADA PT. TRI TUNGGAL PERMAI DI KOTA DUMAI - Septiadi, Dedi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Program Jamsostek mandated by the Indonesian Government Regulation No.14 Year 1993 on the Implementation of the program Jamsostek, consisting of AccidentInsurance, Death Benefit, Old Age Security, and Health Insurance, in which the programmust be implemented for each company. PT. Tri Tunggal Permai is one company thatalso runs the program. To find out the program implementation JamsostekWorkers in Certain Time PT. Tri Tunggal Permai, the authors intend to conductresearch. The formulation of the problem, namely: (1) Knowing the setting procedurekepersertaan Jamsostek Workers at the specific time PT. Tri Tunggal Permai (2)Knowing the program implementation Jamsostek Workers at the specific time PT. TriTunggal Permai (3) Knowing what legal efforts of workers PT. Tri TunggalPermai if the participant dues deduction Jamsostek not with a predetermined. Researchobjectives are:(1) To determine the arrangements and procedures forparticipation of workers at any given time PT. Tri Tunggal Permai in the fieldJamsostek (2) To determine the implementation of the program Jamsostek at anygiven time by the workers PT. Tri Tunggal Permai (3) To know the legal remedyof an employee PT. Tri Tunggal Permai.This study took location in PT. Tri Tunggal Pemai in the town of Dumaithe methods used in evaluating and sampling is purposive sampling method,which sets out a number of samples existing population, the sample categoriesdefined by the author. This type of research is sociological, materials researchcarried out by conducting field surveys to conduct observation and data collectiontools observation, interviews, and literature review.From the results of this study concluded that the Arrangement and theprocedures of participation Jamsostek of workers at any given time PT. TriTunggal Permai in accordance with the Government Regulation of the Republicof Indonesia Number. 14 of 1993 on the Implementation Program Jamsostek,known that certain time workers PT. Tri Tunggal Permai against membership inthe Health Insurance Program, Old Age Security, Employment Insuranceaccident, the answer enrolled Security Death of 20 (twenty) with a percentage of100% (one hundred percent).In the implementation of the program Jamsostek inPT. Tri Tunggal Permai concerning the amount of Social Security contributionspieces running less well with the discovery of two (2) people working who paydues deduction exceeds the social security provisions established. This is becauseemployers mistake when cutting dues Jamsostek workers. Employers acting in good faith to resolve this matter. Settlement of this problem is through themediation and reached an agreement that employers change their loss against thedues deduction Jamsostek workers that exceed provisions.Keywords : - Time Workers - Jamsostek